Sistem Informasi Absensi Mahasiswa Magang Menggunakan PHP dan MySQL Berbasis Web di STMIK AMIK Dumai - Wulan Indriyani; Tetuko Catur Adi Kencono; Pulla Pandika Widodo (UIN Imam Bonjol Padang, 2023)
STMIK AMIK Dumai is a private tertiary institution engaged in the field of education in Indonesia that organizes internships for students in government and private institutions. Currently STMIK AMIK Dumai does not have a system that can manage student internship data and still uses a diary. This manual method is still ineffective for taking attendance and writing daily activities without evidence of activity. The purpose of this research is to design a website-based apprentice attendance application with software PHP and database MySQL. The aim is to monitor attendance, licensing and daily activities of apprentice students during working hours in government and private agencies. So that the entire process and management of internship information can run properly and accurately with photo evidence of activities. The method used in this study is the waterfall method, this method basically accurately describes the situation at the internship location for each student. The application of this internship attendance application is able to improve attendance accuracy and make daily activities more systematic to achieve efficiency.